(untitled) (Historia, 2021)
This article sets out to analyse the role of pulpit preaching in the struggle towards the re-emergence of multi-party democracy in Kenya. It argues that through "pulpit power", certain clerics, notably David Gitari, Alexander Muge, Henry Okullu and Timothy Njoya, initiated a process of transformation as individual activists at a time when the state had effectively silenced voices that demanded political change. It then moves on to chronicle David Gitari’s sermons as a case in point to demonstrate that his political sermons promoted a culture of defiance in the country and marked the genesis of the so called "second liberation" in Kenya. It relies on archival sources and correspondence material as well as a number of searching in-depth oral interviews.